The Interplay of Human Trafficking and the Rohingya Refugee Crisis in Aceh Province, Indonesia: Exploring the Complexities of Criminality and Humanitarian Concerns - Aiyub Kadir, M. Yakub; Rosmawati; Listriani, Sophia; Mail, Syed Muhammad Huzaif (Magister of Law, Faculty of Law, University of Mataram, 2024)
This article delves into the long-standing atrocities committed by the Myanmar government against the Rohingya people in Rakhine province, which have resulted in a significant influx of Rohingya refugees into various regions, including Aceh province, Indonesia. The article aims to investigate the nature of this crisis, particularly focusing on the modus operandi of human trafficking, through a doctrinal-empirical approach. This approach involves observations and interviews with stakeholders involved in the field. The article also highlights the conflicting perspectives surrounding humanitarian and trafficking issues, shedding light on the challenges faced. Despite the existence of Presidential Decree 125/2016, the management of refugee handling remains inconsistent, given the uncertain situation and half-hearted treatment. Consequently, this has led to the expansion of trafficking networks, victimizing both local individuals assisting refugees at sea and on land. Indonesian authorities have predominantly addressed trafficking under immigration law rather than from a humanitarian standpoint. This approach has had adverse effects, resulting in resistance and rejection of Rohingya refugees in Aceh province. Considering that trafficking has emerged as a downstream impact of the global refugee crisis, the perception of viewing trafficking in Rohingya solely as a crime should be questioned. Urgently, a new paradigm and legal regime for refugees in Indonesia are required to address these pressing issues.